Peran Koperasi “Agar Makmur Sentosa” dalam Pengembangan Usaha Budidaya Rumput Laut di Dusun Tlocor, Desa Kedungpandan, Kec. Jabon, Kab. Sidoarjo - Sabrina Ade Ulina Saragih; Ananta Prathama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The limitations in the development of seaweed cultivation business require development with the involvement of the government, seaweed associations, private sector cooperation and through business entities in the form of cooperatives. The Agar Makmur Sentosa Cooperative was formed because of the awareness that seaweed farmers in Tlocor were not yet fully prosperous even though there was great potential for seaweed cultivation as an export commodity. The purpose of this study was to describe the role of the